2019
DOI: 10.1016/j.langsci.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

How to speak “geocentric” in an “egocentric” language: A multimodal study among Ngigua-Spanish bilinguals and Spanish monolinguals in a rural community of Mexico

Abstract: It has recently been shown that individuals residing in rural, indigenous communities rely on geocentric conceptualizations of space, e.g., north/south/east/west, even after they have shifted to a language that is known to favour egocentric conceptualizations, e.g., right/left. In this paper we explore how this combination works in practice by conducting a study in a previously non-investigated indigenous community of Mexico, the Ngiguas. We used a verbal localization task for community-scale relations. We fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 36 publications
3
20
2
3
Order By: Relevance
“…Thus, egocentric and allocentric FoR vocabulary may function differently: Mastering egocentric words may crystallize and promote a strategy that is initially dispreferred, whereas mastering allocentric words may serve merely to put a label on a prepotent preference. A prediction that follows from this account—and one consistent with recent findings (Calderón et al, 2019; Le Guen, 2011)—is that allocentric behavior may occur with or without support from allocentric language, while egocentric behavior may be found only where linguistic and cultural support is in place.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Thus, egocentric and allocentric FoR vocabulary may function differently: Mastering egocentric words may crystallize and promote a strategy that is initially dispreferred, whereas mastering allocentric words may serve merely to put a label on a prepotent preference. A prediction that follows from this account—and one consistent with recent findings (Calderón et al, 2019; Le Guen, 2011)—is that allocentric behavior may occur with or without support from allocentric language, while egocentric behavior may be found only where linguistic and cultural support is in place.…”
Section: Discussionsupporting
confidence: 83%
“…While it may seem surprising that we did not see effects of the other linguistic factors, recent work on bilingualism in gesture has found that monolinguals and bilinguals from the same population do not necessarily differ in their gestural styles (e.g., Calderón, et al, 2019) and that bilinguals do not necessarily switch gestural patterns when switching languages (e.g., So, 2010). Results from this literature have been mixed, however (Gullberg, 2012).…”
mentioning
confidence: 70%
See 3 more Smart Citations